Pengembangan Perangkat Pembelajaran IPA SMP Berbasis Discovery Learning Berorientasi Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik - Syamsir, Muflihah; Danial, Muhammad; Syahrir, Muhammad (Chemistry Education Review (CER), 2020)
This study is development research, which aims at developing and produce IPA learning tools for SMP based on discovery learning in acidic solution, base and salt. The development model used in research to develop discovery learning based learning tools is the 4-D model by Thiagarajan. The limited test of discovery learning-based learning devices was conducted at SMPN 36 Makassar. The research subject was grade VII IPA with 24 students. Data collection techniques are non-test techniques and test techniques. The results of the study reval that (1) the process of learbing tools development utilizes 4-D model consists of 4 stages, namely (a) defining stage (define), (b) the designing stage (design), (c) the development stage (develop), and (d) the dissemination stage (desseminate). (2) the learning tools are valid, practical and effective. The learning tools are stated as practicial because the learning tools implementation is in entirely implemented category, the teacher’s response on learning tools is in very positive category. The learning tools are effective because it has met effectiveness criteria with the teacher's result in learning management is in very high category, the student’s activity is in learning management is in very good category, the student’s activity is in learning management is in very positive category, the results of students’ critical thinking skills has the average of 85.17 with classical completencess 85.95%, the improvment of critical thinking skills based on the N-gain test of 0.82 with high criteria, the learning outcomes has the average of 84.07 with a classical completeness 85.33%, whereas, the improvement in learning outcomes based on the N-gain test is 0.86 with high criteria.